2017
DOI: 10.1002/clen.201500802
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Removal of Heavy Metals From Leachate Contaminated Soil Using Bioaugmentation Process

Abstract: Bioremediation of soil contaminated with metals from leachate is a complex process because it requires understanding the microbial interaction common to such contaminated environment. Therefore, this study tried to enhance the reduction of some extractable metals such as Pb, Cu, and Al through bioaugmentation with inocula of bacterial species isolated from leachate‐contaminated soil. Assessment of metal concentrations in the soil was carried out through characterization (US EPA 3050B test method). Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…A study on removal of extractable metals such as Pb, Cu, and Al through bioaugmentation conducted with inocula of bacterial species isolated from leachate-contaminated soil has shown that the efficiency of metal removal was significantly lower when all isolated microbes were used than when only three species were used ( Lysinibacillus sp., Bacillus sp., and Rhodococcus sp.) [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study on removal of extractable metals such as Pb, Cu, and Al through bioaugmentation conducted with inocula of bacterial species isolated from leachate-contaminated soil has shown that the efficiency of metal removal was significantly lower when all isolated microbes were used than when only three species were used ( Lysinibacillus sp., Bacillus sp., and Rhodococcus sp.) [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are bacterial strains with no IAA and siderospores production ability, and no ACC deaminase activity, which have enhanced metal uptake and accumulation in plant organs. Bioremediation technologies are necessary for the detoxification of metal-contaminants in polluted environments (Emenike et al, 2018a,b), to prevent their toxic effects on the environment and living organisms.…”
Section: Microbial Remediation Of Environmental Pollutionmentioning
confidence: 99%